Identification Of Factors Affecting The Quality Of Life In Hypertension Patients - Yeni Yulianti; Teten Tresnawan; Yosep Purnairawan; Susilawati; Arneta Oktavia (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
The prevalence of hypertension continues to increase, around 2.31 billion people in the world have hypertension. According to Barudin, et al (2021), hypertension significantly affects quality of life, patients suffering from hypertension who do not manage themselves properly have a poor quality of life. Patients who suffer from hypertension with comorbidities or complications tend to experience a decrease in quality of life, such as in physical, psychological, social, and environmental aspects (Alfian et al., 2017). This study aims to identify the factors that affect the quality of life of hypertensive patients in the Subangjaya Village, the Working Area of UPTD Sukabumi, Sukabumi City. Factors that can affect the quality of life include: gender, age, education level, employment status, length of suffering, and self-management. This research is a correlational study with a cross sectional approach with a total sample of 136 respondents. Total sampling way of taking research samples. Hypothesis analysis in this study used Chi-Square and logistic regression tests. The results of this study identified no relationship between age, gender, employment status, and duration of suffering from hypertension with quality of life because it had a P-value > 0.05, and there was a significant relationship between self-management and quality of life with a P value -value 0.000 and correlation value (OR) 12.632. It is hoped that the UPTD Sukabumi Health Center can improve health education regarding the importance of self-management of hypertension sufferers.